Physical Adsorption of the Quantum Gas - Kim, Un Sik (1972)
The significant structure theory of quantum liquids such as hydrogen, deuterium, and helium has been applied to the physical adsorption occurring in the submonolayer region. The partition function for the two-dimensional adsorbed fluid has been derived. The properties of isothermal and isosteric heat show good agreement with the available data from the literature.